Medical sales representatives: a neglected group of pharmaceutical workers in India: need to redefine their role in post COVID-19 world - Dixit, Sushmita (International Journal Of Community Medicine And Public Health, 2023)
Purpose of the study was to analyze the challenges of medical sales representatives’ occupation in India and identification of the impact of digital technologies in redefining the role of medical sales representatives in post-COVID era in India. In this study, relevant literature is reviewed to know the past and present situation of the Medical sales representative’s occupation in India and digital intervention in it during COVID-19 pandemic. The study found that digital technologies are proving significant in reshaping and redefining the occupational role of medical sales representatives’ role in post COVID-19 world. The study suggests transformational route for medical sales representatives’ conventional role through digital learning.